The role of analytical customer relationship management in improving the quality of banking service: A case study of the Algerian Agriculture and Rural Development Bank – Bechar Agency - Nawel, Seddiki (International journal of economic perspectives, 2024)
This study aims to shed light on Customer Relationship Management (CRM) in general, with a particular focus on analytical CRM considering that it is a contemporary marketing concept, and its relationship and the extent of its impact on the quality of service within banking institutions. For that purpose, the research specifically focused on the dimensions of analytical CRM, which consists of customer knowledge, customer value, and customer segmentation. We followed a descriptive analytical approach, utilizing a questionnaire as the primary data collection tool. We distributed 40 questionnaires, of which 38 were suitable for analysis; and through this study, we concluded that analytical customer relationship management affects improving the quality of banking service at the Algerian Agricultural and Rural Development Bank in Bechar.